"THE MODULATION OF ORAL DISEASE DEVELOPMENT BY FACTORS OF THE LOCAL IMMUNE SYSTEM IN INDIVIDUALS PRESENTING WITH CHRONIC RENAL INSUFFICIENCY." (World Bulletin of Public Health, 2026)
In many cases, systemic diseases show their first signs in the oral cavity. Currently, dental diseases are most closely studied in patients with chronic renal failure at different stages.
Keywords: chronic renal failure; periodontitis; lactoferrin; chronic kidney disease